Two degree of freedom control scheme for unstable processes with small time delay. (May 2015) - Ajmeri, Moina; Ali, Ahmad
Abstract: In this work, a recently reported two degree of freedom control structure namely the Parallel Control Structure (PCS) is modified to achieve improved control performance for unstable processes. New tuning rules are proposed using a direct synthesis approach for unstable first order plus time delay (UFOPTD), unstable second order plus time delay (USOPTD) and integrating and unstable plus time delay (IUPTD) process models. The proposed method has two tuning parameters whose suitable values are recommended after studying their effect on the system performance and robustness. This is an advantage of the present work over the other reported control schemes where the authors provide suitable ranges of the tuning parameters values. Simulation examples show that the present scheme results in improved nominal and perturbed responses as compared to the recently reported methods. Also it is observed that satisfactory performance is achieved when the proposed tuning rules are applied on an isothermal chemical reactor which exhibits multiple steady state solutions. Highlights: Recently reported two degree of freedom control structure namely the Parallel Control Structure is modified to achieve improved control performance for unstable processes with time delays The controllers of the modified PCS are designed using the direct synthesis approach for a class of unstable processes. After studying the effect of tuning parameters on the system performance and robustness suitable values of the tuning parameters are recommended. Five examples are given to show the superiority of the proposed control scheme as compared to the recently reported strategies.